The world almanac and book of facts 2004 (World Almanac Books, 2004)
The World Almanac and Book of Facts 2004" packs a lot of information into its 1008 pages. The book is well organized and easy to use. Included are three separate indexes: an extensive general index, a quick reference index, and (on the back cover) a quick thumb index. The book covers information in many different areas: the U.S. government, world history, religion, science and technology, sports, etc.